Plasma transfer arc welding (PTAW) for depositing tungsten carbide-nickel cermet coating for corrosion - Kamdi, Zakiah (Penerbit UTHM, 2020)
PTAW is a cermet deposition method that may produce thick coating (up tp 3 mm). Cermet deposit by this method has shown high wear and corrosion resistance. The tungsten carbide (WC) content will be varied (0, 35, 50 65 wt%) to evaluate its morphology, chemical composition and corrosion behavior of the coating. Two techniques have been used to characterise the powders and coatings which are scanning electron microscopy (SEM) and x-ray diffraction (XRD). Micro-scale abrasion wear tester and dry sand rubber wheel has been used for wear behaviour evaluation. It is found that, for all coatings with WC, XRD spectrum shows two type of tungsten carbide which are WC and W2C, nickel (Ni) and nickel boride (Ni3B). By increasing the WC contents, the WC distributions are more homogeneous. Lower WC content shows the WC are tend to sinking to the bottom layer of the coating due to its high density compare to the nickel. The corrosion result shows that by increasing the carbide content, not much changes to the corrosion potential. The corrosion for cermet coating is due to removal of binder follow by carbide detachment. The corrosion in acidic electrolyte is higher compares to in alkaline electrolyte.